2018
DOI: 10.1038/s41598-018-28192-5
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endophytes from arid areas of Andalusia: high potential sources for antifungal and antitumoral agents

Abstract: Native plant communities from arid areas present distinctive characteristics to survive in extreme conditions. The large number of poorly studied endemic plants represents a unique potential source for the discovery of novel fungal symbionts as well as host-specific endophytes not yet described. The addition of adsorptive polymeric resins in fungal fermentations has been seen to promote the production of new secondary metabolites and is a tool used consistently to generate new compounds with potential biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 67 publications
(73 reference statements)
4
34
0
Order By: Relevance
“…Endophytic fungi in plants are microorganisms that parasitize symbiotically in the internal tissues during the whole or part of their life cycles of the hosts without causing apparent pathogenic symptoms [1], but may turn pathogenic during host senescence [2]. Accumulated evidence has confirmed that plant endophytes from special orextreme environment has many effects on host ecological adaptability [3][4][5]. It is well known that the concurrence of endophytes may accelerate plant growth and increase the survival rate of biotic or abioticstresses, such as plant diseases, pests, drought, salinity and extreme temperatures [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi in plants are microorganisms that parasitize symbiotically in the internal tissues during the whole or part of their life cycles of the hosts without causing apparent pathogenic symptoms [1], but may turn pathogenic during host senescence [2]. Accumulated evidence has confirmed that plant endophytes from special orextreme environment has many effects on host ecological adaptability [3][4][5]. It is well known that the concurrence of endophytes may accelerate plant growth and increase the survival rate of biotic or abioticstresses, such as plant diseases, pests, drought, salinity and extreme temperatures [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Alignment gaps were taken as missing characters. Bootstrap analysis (1000 bootstrap) was executed to deduce the consensus tree for the demonstration of evolutionary relationship (Kapoor and Saxena, 2014;González-Menéndez et al, 2018).…”
Section: Sequence Assembly and Phylogenetic Identificationmentioning
confidence: 99%
“…In a recent work with 349 fungal endophytes, we studied the effect of the addition of adsorptive polymeric resins based on styrene-divinylbenzene matrix during fungal fermentations to increase the production titers of some SMs and the chemical diversity of the molecules produced by these fungi [15]. In the same way, the addition of several epigenetic modifiers belonging to both classes of DNA methyltransferase (DNMT) and histone deacetylase (HDAC) inhibitors, in a subset of diverse endophytic fungi was shown to promote the induction of secondary metabolite pathways, otherwise silent under standard culture conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of our natural product screening programme targeted at discovering new antimicrobial compounds, we applied an OSMAC approach that included the use of adsorptive polymeric resins in fermentations of a large set of fungal endophytes isolated from plants collected in arid areas of Andalusia. As a result of this screening, we observed the production of antimicrobial activities from the extracts of Dimorphosporicola tragani CF-090383, when only grown in presence of styrene-divinylbenzene resins [15]. For this reason, we decided to perform an in depth study of this fungal endophyte and assess the effect of multiple nutritional conditions and the addition of metabolic effectors on the bioactive secondary metabolite diversity.…”
Section: Introductionmentioning
confidence: 99%